Multi-metal series catalyst as well as preparation method and application thereof

By using multimetal tandem catalysts in DBFC, combining carbon material-supported precious metal nanoparticles and bimetallic hydrotalcite materials, the problems of low activity of the anode catalyst and serious competitive reactions are solved, and efficient fuel electrooxidation and low-cost production are achieved.

CN119601684APending Publication Date: 2025-03-11FUDAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411631193.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In direct sodium borohydride fuel cells (DBFCs), the anode catalyst activity is relatively low and the competition reaction is severe, resulting in low fuel energy utilization and high cost.

Method used

A multi-metal tandem catalyst is used, composed of precious metal nanoparticles supported by carbon material and bimetallic hydrotalcite material, which improves catalytic activity and inhibits side reactions through a step-by-step catalytic mechanism.

Benefits of technology

High electron transfer number and high power density are achieved, and the utilization rate of borohydrogen fuel is significantly improved, reducing the amount of precious metals and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601684A_ABST
    Figure CN119601684A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fuel cells, and particularly relates to a multi-metal series catalyst and a preparation method and application thereof. The multi-metal series catalyst is composed of two structures, wherein one structure is a transition bimetal-based hydrotalcite material and is of a sheet structure; and the other one is noble metal nanoparticles uniformly dispersed on the carbon material, and the average size is less than 10 nanometers. The prepared series catalyst is applied to sodium borohydride electrooxidation reaction, the bimetal-based hydrotalcite material is used as an active site for borohydride adsorption and preliminary oxidation, and the noble metal nanoparticles are used as an active site for further oxidation of a preliminary oxidation product of borohydride. As the anode catalyst of the direct fuel cell, the anode catalyst not only has high electron transfer number, but also shows relatively high power density. Compared with other common catalysts, the use amount of precious metal is low, the preparation method is simple and controllable, and high application value is shown in the field of direct hydroboron fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a multi-metal series catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen has been widely studied in the energy field because of its clean, green and renewable characteristics. However, hydrogen has many problems, such as its flammable and explosive properties that make storage and transportation difficult, so it is difficult to achieve large-scale application in fuel cells in a short period of time. Compared with hydrogen, sodium borohydride not only has a high hydrogen content (10.6wt%), but also exhibits a high energy density (9.3Wh g -1 ), and at the same time, it has the advantages of being safe, non-toxic and stable, so it is regarded as an effective substitute for hydrogen and is widely used in direct sodium borohydride fuel cells (DBFC).

[0003] Compared with other liquid fuel cells such as methanol, DBFC has higher open circuit voltage and energy density. Although DBFC has been studied for many years, it still faces problems such as low anode catalyst activity and serious competitive reactions. At present, the commonly used anode catalysts for DBFC are platinum metals. This type of metal has high activity for the sodium borohydride electro-oxidation reaction (BOR), but due to its strong adsorption energy for hydrogen, side reactions such as hydrogen evolution reaction (HER) and sodium borohydride hydrolysis reaction are more serious, which reduces the energy utilization of fuel. In addition, this type of material is relatively expensive, which greatly limits its application in direct sodium borohydride fuel cells. Therefore, how to develop a BOR catalyst with high activity, high electron transfer number and low price is particularly urgent. Summary of the invention

[0004] In order to overcome the difficulties faced in the above-mentioned fields, the purpose of the present invention is to provide a multi-metal tandem catalyst with high activity and high electron transfer number, and its preparation method and application, by means of the step-by-step catalytic effect of the tandem catalyst, while improving the electro-oxidation activity of the catalyst for borohydride fuel, effectively inhibiting the occurrence of side reactions, thereby achieving high fuel utilization.

[0005] The multi-metal tandem catalyst provided by the present invention consists of two parts: noble metal nanoparticles (average size less than 10 nanometers) with a particle size of 5-15nm, which are supported on a carbon material as a substrate and are evenly dispersed (a first catalyst), and a bimetallic hydrotalcite material in a flaky form (a second catalyst); in the sodium borohydride electro-oxidation reaction, the bimetallic hydrotalcite material serves as an active site for the adsorption and preliminary oxidation of boron hydride molecules, and the noble metal nanoparticles serve as active sites for further oxidation of the preliminary oxidation products of the boron hydride molecules; the mass ratio of the carbon-supported noble metal nanoparticles to the bimetal in the hydrotalcite material is 1:(20-40); and the average size of the carbon material is 20-60nm.

[0006] Further:

[0007] The noble metal nanoparticles are one of Pt, Pd, Au, Ru, and Rh;

[0008] The bimetallic hydrotalcite material contains two different kinds of bimetallic materials selected from Co, Fe, Ni, Mg, Al, Zn, Cu and Cr. Preferably, the molar ratio of the two metals is 1:3 to 1:40; more preferably, the molar ratio of the two metals is 1:3 to 1:25.

[0009] The carbon carrier is one of multi-walled carbon nanotubes, conductive carbon black XC-72, graphite, conductive carbon black BP2000, and activated carbon.

[0010] The present invention also provides a method for preparing the multi-metal tandem catalyst, which is synthesized by a two-step method, and the specific steps are:

[0011] (1) dispersing the carbon material carrier in a solvent, ultrasonicating for 10-40 minutes to obtain a suspension; then adding a precursor solution of a precious metal element, and stirring for 10-20 minutes; then slowly dropping an alkaline solution with a concentration of 20-40wt% into the precursor solution, stirring for 6-15 hours, collecting solid particles by suction filtration and drying, thereby obtaining a precious metal precursor supported on the carbon material;

[0012] (2) Weigh the above-mentioned noble metal precursor loaded on the carbon material, add it to the dispersion, and ultrasonicate for 5-20 minutes; then, add the metal salt precursor and additives, place it in a 65-90°C water bath, stir for 6-20 hours, and after the reaction is completed, filter and collect the solid material, and dry it to obtain a multi-metal tandem catalyst.

[0013] Further:

[0014] In step (1), the solvent is at least one of ethanol, ethyl acetate, isopropanol, ethylene glycol, acetone, and water;

[0015] In step (1), the precursor solution of the noble metal element is one of the hydrochloride, nitrate, acetate or chlorate of Pt, Pd, Au, Ru or Rh;

[0016] In step (1), the alkaline solution is one of sodium hydroxide solution, potassium hydroxide solution, sodium sulfide solution, sodium carbonate solution, potassium carbonate solution, and ammonia water;

[0017] In step (2), the dispersion liquid is at least one of ethanol, ethyl acetate, isopropanol, ethylene glycol, acetone, and water;

[0018] In step (2), the metal salt precursor is at least two of the hydrochlorides, nitrates, acetates or chlorates of Co, Fe, Ni, Mg, Al, Zn, Cu and Cr;

[0019] In step (2), the additive is one of polypyrrolidone, urea, hexamethylenetetramine, sodium dodecylsulfonate, and hexadecyltrimethylammonium bromide.

[0020] The multi-metal tandem catalyst provided by the present invention can be used to prepare an electrode material for a three-electrode system for catalyzing electro-oxidation of boron hydride fuel. The electrode material consists of an electrode substrate and a multi-metal tandem catalyst layer coated on the electrode substrate; the electrode substrate is one of transparent conductive glass, glassy carbon electrode and conductive metal sheet; the effective area of ​​the conductive substrate is 0.02-0.2 cm 2 The loading amount of the catalyst layer in the electrode is 0.05-1 mg / cm 2 .

[0021] The present invention provides a method for preparing the above electrode material, the specific steps of which are:

[0022] First, the multi-metal tandem catalyst is added to a mixed solution of a binder and an organic solvent, and ultrasonicated for 10-50 minutes to obtain a uniformly dispersed catalyst slurry. A certain amount of the catalyst slurry is dropped onto an electrode substrate and dried at room temperature for 2-10 hours to serve as a working electrode material for a catalyst boron hydride fuel electro-oxidation three-electrode system.

[0023] Furthermore, the binder is one of a perfluorosulfonic acid resin solution, a polyvinylidene fluoride solution, a polytetrafluoroethylene solution, and a polyacrylic acid solution;

[0024] Furthermore, the organic solvent is one of methanol, ethanol, ethyl acetate, isopropanol and dimethyl sulfoxide.

[0025] The multi-metal tandem catalyst provided by the present invention can also be used to prepare an anode electrode material for a boron hydrogen fuel cell. The anode electrode material is composed of a conductive substrate and a multi-metal tandem catalyst layer coated on the conductive substrate; the conductive substrate is one of carbon cloth, carbon paper, metal felt and metal foam; the thickness of the conductive substrate is 1-2 mm, and the area of ​​the conductive substrate is 2-5 cm 2 The loading amount of the catalyst layer in the electrode is 0.5-6 mg / cm 2 .

[0026] The present invention provides a method for preparing the above electrode material, the specific steps of which are:

[0027] Firstly, a multi-metal tandem catalyst and a binder are added to an organic solvent, and after ultrasonic treatment for 30-60 minutes, the catalyst is loaded onto an electrode substrate; after drying at 50-70°C, the catalyst is used as an anode electrode of a single sodium borohydride fuel cell at room temperature.

[0028] Furthermore, the binder is one of perfluorosulfonic acid resin solution, polytetrafluoroethylene solution, and polyimide solution; and the organic solvent is one of methanol, ethanol, acetonitrile, acetone, and isopropanol.

[0029] The present invention also provides a fuel cell testing device under normal temperature conditions, using the above-mentioned electrode as the anode of the fuel cell, using a platinum carbon catalyst with a platinum content of 20-50wt% as a cathode catalyst, using a proton exchange membrane with a thickness of 10-200μm as a diaphragm, and a carbon paper with a hydrophobic layer as a cathode gas diffusion layer. The anode uses 1-5wt% boron hydrogen fuel and 5-15wt% alkali mixed solution as fuel, and the effective area of ​​the plate is 0.1-2cm 2 , pure oxygen was introduced into the cathode, the gas flow rate was 50-200 mL / min, and the test temperature was room temperature.

[0030] The multi-metal tandem catalyst provided by the present invention can also be used to prepare a membrane electrode material for a boron hydrogen fuel cell. The membrane electrode has an efficient mass transfer process, effectively promotes the electro-oxidation process of boron hydrogen fuel, and realizes a continuous and stable output of the fuel cell. The membrane electrode material is composed of a proton exchange membrane, a multi-metal tandem catalyst layer coated on the proton exchange membrane, and a cathode catalyst layer; the thickness of the proton exchange membrane is 10-80 μm; the cathode catalyst is a platinum carbon catalyst with a mass fraction of 20-70%, and the loading amount of the catalyst layer in the membrane electrode is 0.2-3 mg / cm 2 .

[0031] The present invention provides a method for preparing the above membrane electrode, the specific steps of which are:

[0032] First, the multi-metal tandem catalyst and the cathode catalyst are added to the mixed solution of the binder solution and the organic solvent respectively, and after ultrasonic treatment for 10-50 minutes, a uniformly dispersed multi-metal tandem catalyst slurry and a cathode catalyst slurry are obtained. The above catalyst slurries are sprayed on both sides of the proton exchange membrane respectively, and the spraying effective area is 0.5-2cm 2 ; After being fully dried at 50-70℃ in air, it can be used as membrane electrode material for boron hydride fuel cells.

[0033] Furthermore, the binder is one of a perfluorosulfonic acid resin solution, a polyvinylidene fluoride solution, a polytetrafluoroethylene solution, and a polyacrylic acid solution;

[0034] Furthermore, the organic solvent is one of methanol, ethanol, ethyl acetate, isopropanol and dimethyl sulfoxide.

[0035] The present invention also provides a fuel cell testing device for use under high temperature conditions, which uses the multi-metal series catalyst as the anode of the fuel cell, a platinum-carbon catalyst with a platinum content of 20-70% as the cathode catalyst, an ion exchange membrane with a thickness of 10-30 μm as the diaphragm, a graphite plate engraved with a serpentine flow field as the cathode and anode plates, carbon paper with a hydrophobic layer as the cathode gas diffusion layer, the anode uses 0.3-3 mol / L boron hydrogen fuel and 0.5-3 mol / L alkali mixed solution as fuel, the cathode is fed with air, the back pressure is 0.1-0.3 MPa, the gas flow rate is 100-500 mL / min, and the test temperature is 80°C.

[0036] The tandem catalyst prepared by the present invention is used for sodium borohydride electro-oxidation reaction, the bimetallic hydrotalcite material serves as an active site for borohydride adsorption and preliminary oxidation, and the noble metal nanoparticles serve as an active site for further oxidation of the preliminary oxidation product of borohydride. As a direct fuel cell anode catalyst, the present invention not only has a high electron transfer number, but also exhibits a high power density. Compared with other common catalysts, the present invention has a lower amount of noble metal, a simple and controllable preparation method, and exhibits a high application value in the field of direct borohydride fuel cells.

[0037] Compared with the existing technology in this field, the technical solution of the present invention has the following characteristics and advantages:

[0038] (1) The multi-metal tandem catalyst provided by the present invention is mainly composed of non-precious metals, and the raw materials are cheap and widely available, and the amount of precious metals used is low, so the catalyst is inexpensive; in addition, the preparation method is simple, effective and controllable, and the prepared catalyst has the advantages of high activity and high selectivity, which is conducive to mass production and industrial application, and has a higher competitive advantage than the catalysts currently reported;

[0039] (2) The multi-metal tandem catalyst has a clear structure, has a high electron transfer number and a high fuel utilization rate, and has a high power density and exhibits a strong catalytic oxidation ability for boron hydride fuel.

[0040] (3) The multi-metal tandem catalyst provided by the present invention can achieve a relatively thorough oxidation process of boron hydride molecules at a relatively low potential. The catalyst is mainly composed of two structures, including a carbon material as a substrate, with small-sized precious metal nanoparticles evenly dispersed, and a bimetallic hydrotalcite material in a flaky form; the bimetallic hydrotalcite material serves as an active site for the adsorption and initial oxidation of boron hydride molecules, while the precious metal nanoparticles serve as an active site for further oxidation of the initial oxidation products of boron hydride molecules, which is conducive to a relatively thorough oxidation process. The two structures work synergistically, ultimately achieving high selectivity and high power density of the catalyst, providing a new approach for the development of high-efficiency catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is the X-ray diffraction (XRD) pattern of the CoFe&AuC catalyst in the embodiment of the present invention.

[0042] Figure 2 This is a scanning electron microscope (SEM) photograph of the CoFe&AuC catalyst in the embodiment of the present invention.

[0043] Figure 3 This is a transmission electron microscope (TEM) photograph of the CoFe&AuC catalyst in the embodiment of the present invention.

[0044] Figure 4 This is the energy spectrum distribution (EDS) of the CoFe&AuC catalyst in the embodiment of the present invention.

[0045] Figure 5 This is the X-ray photoelectron spectrum (XPS) of the CoFe&AuC catalyst in the embodiment of the present invention.

[0046] Figure 6 This is the electrochemical impedance spectroscopy (EIS) of the CoFe&AuC catalyst in the embodiment of the present invention.

[0047] Figure 7 1 is the cyclic voltammetry (CV) curve of the CoFe&AuC catalyst in the embodiment of the present invention.

[0048] Figure 8 1 is the linear sweep voltammetry (LSV) curve of the CoFe&AuC catalyst at different rotation speeds in the embodiment of the present invention.

[0049] Fig. 9 The CoFe&AuC catalyst in the embodiment of the present invention is Figure 8The calculated Koutecky–Levich plot is at (0.8 V vs RHE).

[0050] Fig.10 This is the current density-power density curve of the direct sodium borohydride fuel cell with CoFe&AuC catalyst working at room temperature in the embodiment of the present invention.

[0051] Fig.11 This is the current density-power density curve of the direct sodium borohydride fuel cell with CoFe&AuC catalyst working at 80°C in an embodiment of the present invention.

[0052] Fig.12 1 is a current density-power density curve of CoFe&AuC catalysts with different metal ratios in a direct sodium borohydride fuel cell working at room temperature in an embodiment of the present invention.

[0053] Fig.13 Schematic diagram of the catalytic process of the electro-oxidation of sodium borohydride by CoFe&AuC catalyst in an embodiment of the present invention. DETAILED DESCRIPTION

[0054] At present, platinum group metals (PGM) are the most excellent catalytic materials for catalyzing the electro-oxidation reaction (BOR) of sodium borohydride. - Has strong adsorption, can achieve rapid BH4 - Electro-oxidation process, to obtain higher power density in DBFC. However, on the one hand, PGM has low earth reserves and is relatively expensive, which limits its large-scale application; on the other hand, there are competing reactions such as hydrolysis reaction and hydrogen evolution reaction when PGM catalyzes BOR, which reduces the utilization rate of anode fuel and the open circuit voltage in DBFC; in addition, PGM active sites are easily poisoned, resulting in easy deactivation of PGM. Based on this, transition metals such as Co, Fe, Ni and other elements have received more and more research. This type of material is relatively cheap, and compared with PGM, its activity in hydrogen evolution reaction is relatively lower. Although this type of material has high BOR catalytic activity, hydrolysis reaction is also inevitable. Materials such as Au and Ag can effectively inhibit the hydrolysis reaction of sodium borohydride and have high selectivity for BOR. They are considered to be ideal BOR catalysts, but this type of material has low selectivity for BH4 - The adsorption capacity is limited, resulting in low power density in direct sodium borohydride fuel cells.

[0055] The invention provides a multi-metal tandem catalyst. XRD and element distribution diagrams show that the tandem catalyst consists of two phases, the two structures are evenly mixed, and the catalyst plays a step-by-step catalytic role in the electro-oxidation process of sodium borohydride. Electrochemical test results show that the tandem catalyst not only has a low starting potential for BOR catalysis, but also can realize its multi-electron transfer process, and is an ideal BOR catalytic material.

[0056] The present invention will be further explained below by way of embodiments in conjunction with the accompanying drawings.

[0057] Example 1, a multi-metal tandem catalyst CoFe&AuC and its preparation method

[0058] The two-step synthesis uses cobalt, iron and gold as the metal elements. The preparation process of CoFe&AuC catalyst is as follows:

[0059] First, weigh 0.2 g of carbon black powder and add it to a dispersion of 40 mL of ethanol and 40 mL of deionized water, and ultrasonicate for at least 15 min. -1 chloroauric acid solution, add it to the above dispersion and stir evenly. Then, add 1.5 mL of concentrated ammonia water dropwise to the above solution and stir vigorously for at least 10 hours. Use suction filtration to wash and collect the above precipitate. After drying, grind it thoroughly to obtain the precursor AuC catalyst. Take 50 mg of the above AuC catalyst and add it to a mixed solution of 10 mL of ethanol and 90 mL of deionized water. Ultrasonicate for 15 minutes, then add 0.3426 g of cobalt chloride hexahydrate, 0.0119 g of ferrous chloride tetrahydrate and 1.2618 g of hexamethylenetetramine to the above mixed solution and stir for 10 minutes. After that, place the above solution in a 90°C water bath, stir for at least 10 hours, filter, wash and dry to obtain the CoFe&AuC multi-metal tandem catalyst.

[0060] The XRD pattern of the catalyst is shown in Figure 1 . Figure 1 It shows that the main body of the CoFe&AuC catalyst is composed of CoFe LDH and Au, and the main exposed crystal face of Au is (111). SEM ( Figure 2 ) photos and TEM( Figure 3 ) The photo shows that the CoFe&AuC catalyst consists of a flake structure and nanoparticles uniformly dispersed on amorphous clusters. The former is CoFe LDH with a crystal plane spacing of 0.245nm, corresponding to the (104) crystal plane, and the latter is Au grown on carbon black with a crystal plane spacing of 0.235nm, corresponding to the (111) crystal plane. EDS results ( Figure 4) illustrates the uniform distribution of the three elements Co, Fe, and Au, and further proves the uniform mixing of CoFe LDH and AuC components. XPS results ( Figure 5 ) shows that the valence state of Au in CoFe&AuC is mainly 0, which is lower than that of AuC sample; while the valence state of Co in CoFe&AuC is a mixed valence state of +2 and +3, which has no obvious difference from the valence state of CoFe&C; the main form of Fe in CoFe&AuC is Fe 3+ , the valence state is higher than that of CoFe&C.

[0061] In this embodiment, the above-mentioned multi-metal tandem catalyst CoFe&AuC is also provided to prepare a working electrode for a three-electrode system test: specifically, 5 mg of CoFe&AuC catalyst is added to 0.5 mL of ethanol solvent, and then 40 μL of 5 wt% Nafion solution is added. After ultrasonic treatment for 30 minutes, a uniformly dispersed catalyst slurry is obtained. The above-mentioned catalyst slurry is dropped onto a glassy carbon electrode with a diameter of 30 mm, and dried at room temperature to serve as a working electrode material for a three-electrode system using a catalyst sodium borohydride electro-oxidation.

[0062] The electrochemical performance was analyzed and the EIS results are shown in Figure 6 The results show that compared with CoFe&C, the spectrum radius of CoFe&AuC is close to that of AuC and much smaller than that of CoFe&C, indicating that it has a smaller charge transfer impedance, which is conducive to the transfer of charge at the interface. Its CV curve is shown in Figure 7 , Figure 7 The results show that compared with AuC, CoFe&AuC has a distinct BOR oxidation peak and a higher current density, while the oxidation current density of CoFe&C for BOR is lower, indicating that CoFe&AuC has a higher electro-oxidation activity for sodium borohydride. Figure 8 , Fig. 9 and the Koutecky–Levich formula (j -1 =j k -1 +j d -1 =j k -1 +B -1 ω -0.5 , B = 0.62 × n × D 2 / 3 F -1 / 6 c0), the electron transfer number at 0.8 V vs. RHE can be calculated to be 5.4, which illustrates the high selectivity of CoFe&AuC for BOR.

[0063] This embodiment also provides the above-mentioned multi-metal tandem catalyst CoFe&AuC for preparing the anode electrode of a room temperature direct sodium borohydride fuel cell: first, 6 mg of CoFe&AuC catalyst is added to 2 mL of ethanol solvent, and then 80 μL of 5 wt% Nafion solution is added. After ultrasonication for 40 minutes, a uniformly dispersed catalyst slurry is obtained, which is loaded onto nickel foam by spraying, and placed on a 60°C hot plate for drying to serve as the anode electrode of a room temperature direct sodium borohydride fuel cell.

[0064] This embodiment also provides a fuel cell test device operating at room temperature, using the above electrode as the anode of the fuel cell, a platinum carbon catalyst with a platinum content of 40wt% as the cathode catalyst, a proton exchange membrane with a thickness of 183μm as the diaphragm, 28BC carbon paper with a hydrophobic layer as the cathode gas diffusion layer, and a mixed solution of 4wt% sodium borohydride and 12wt% sodium hydroxide as the anode fuel. The effective area of ​​the plate is 1cm 2 , pure oxygen was introduced into the cathode, the gas flow rate was 100mL / min, and the test temperature was room temperature. Fig.10 According to the above test conditions, CoFe&AuC has a current density of 540mA / cm 2 The peak power density reached 290 mW / cm 2 , which indicates that the CoFe&AuC catalyst has high catalytic activity for sodium borohydride electrooxidation at room temperature.

[0065] Example 2: The above multi-metal tandem catalyst CoFe&AuC is used to prepare sodium borohydride fuel cell membrane electrode and tested in a high-temperature fuel cell.

[0066] (1) Preparation of sodium borohydride fuel cell membrane electrode: First, 25 mg of CoFe&AuC catalyst and 40% PtC catalyst were weighed and added to 2 mL of isopropanol solvent, and 180 μL of 5 wt% Nafion solution was added at the same time. Ultrasonication was performed for more than 30 minutes to obtain uniformly dispersed anode slurry and cathode slurry. The above anode slurry and cathode slurry were sprayed on both sides of the proton exchange membrane, respectively, and dried at 60°C. The effective area was 1 cm 2 , as a membrane electrode material for direct sodium borohydride fuel cells.

[0067] (2) Structural composition and test of sodium borohydride fuel cell: The fuel cell is mainly composed of the membrane electrode, carbon cloth, gas diffusion layer, proton exchange membrane, PET material gasket, organic glass insulation plate, graphite flow field, and stainless steel end plate prepared above. A mixed solution of 2 mol / L sodium borohydride and 1 mol / L sodium hydroxide is used as the anode fuel. A peristaltic pump is used for circulating feed at a flow rate of 100 mL / min. Air is introduced into the cathode, the back pressure is adjusted to 0.2 MPa, the gas flow rate is 400 mL / min, and the test temperature is 80°C. Fig.11 According to the above test conditions, the peak power density of CoFe&AuC is 580mW / cm 2 , which indicates that CoFe&AuC has excellent BOR catalytic activity and shows potential application prospects in direct sodium borohydride fuel cells.

[0068] Example 3, comparison of CoFe&AuC catalysts with different metal ratios (Co:Fe).

[0069] This example provides CoFe&AuC catalysts with different metal ratios (Co:Fe) to explore their effects on the electrooxidation activity of sodium borohydride. The method is as follows:

[0070] First, weigh 0.2 g of carbon black powder and add it to a dispersion of 40 mL of ethanol and 40 mL of deionized water, and ultrasonicate for at least 15 min. -1 chloroauric acid solution, add it to the above dispersion and stir evenly. Then, add 1.5mL of concentrated ammonia water dropwise to the above solution and stir vigorously for at least 10 hours, use suction filtration to wash and collect the above precipitate, dry and grind it thoroughly to obtain the precursor AuC catalyst. Take 50mg of the above AuC catalyst and add it to a mixed solution of 10mL ethanol and 90mL deionized water, ultrasonicate for 15min, then add different amounts of cobalt chloride hexahydrate (0.7mmol, 0.65mmol, 0.6mmol, 0.5mmol) and ferrous chloride tetrahydrate (0.05mmol, 0.1mmol, 0.15mmol, 0.25mmol) to the above mixed solution, respectively, so that the total molar amount of the two raw materials is 0.75mmol, then add 1.2618g of hexamethylenetetramine and stir for 10min. After that, place the above solution in a 90℃ water bath, stir for at least 10h, filter, wash and dry, and you can get CoFe&AuC multi-metal tandem catalysts with different metal ratios.

[0071] This example also provides a method for preparing an anode electrode for a room temperature direct sodium borohydride fuel cell:

[0072] Firstly, 6 mg of CoFe&AuC catalysts with different metal ratios were added into 2 mL of ethanol solvent respectively, and then 80 μL of 5 wt% Nafion solution was added. After ultrasonic treatment for 40 minutes, a uniformly dispersed catalyst slurry was obtained. The slurry was loaded onto nickel foam by spraying and dried on a hot plate at 60°C to serve as the anode electrode of a single cell of direct sodium borohydride fuel at room temperature.

[0073] The present invention also provides a fuel cell testing device operating at room temperature, using the electrode prepared by the above-mentioned CoFe&AuC catalyst with different metal ratios as the anode of the fuel cell, a platinum carbon catalyst with a platinum content of 40wt% as the cathode catalyst, a proton exchange membrane with a thickness of 183μm as the diaphragm, 28BC carbon paper with a hydrophobic layer as the cathode gas diffusion layer, and a mixed solution of 4wt% sodium borohydride and 12wt% sodium hydroxide as the anode fuel. The effective area of ​​the plate is 1cm 2 , pure oxygen was introduced into the cathode, the gas flow rate was 100mL / min, and the test temperature was room temperature. Fig.12 According to the above test conditions, when the Co:Fe molar ratio is 14:1, 6.5:1, 5:1, and 4:1, the peak power density of the catalyst is 200 mW / cm 2 、190mW / cm 2 、176mW / cm 2 、158mW / cm 2 ,The results show that as the Co:Fe feed ratio in CoFe&AuC increases, the peak power density of the catalyst gradually decreases.,Combined with Example 1, when the molar ratio of the two metals is 24:1, the performance is optimal and the highest power density can be obtained.

Claims

1. A multi-metal tandem catalyst, characterized in that: The invention consists of two parts: noble metal nanoparticles with a particle size of 5-15 nm uniformly dispersed on a carbon material, and a bimetallic hydrotalcite material in a flaky form; in the sodium borohydride electro-oxidation reaction, the bimetallic hydrotalcite material serves as an active site for the adsorption and initial oxidation of boron hydride molecules, and the noble metal nanoparticles serve as an active site for further oxidation of the initial oxidation products of boron hydride molecules; the mass ratio of the carbon-supported noble metal nanoparticles to the bimetal in the hydrotalcite material is 1:(20-40); and the average size of the carbon material is 20-60 nm.

2. The multi-metal tandem catalyst according to claim 1, characterized in that: The noble metal nanoparticles are one of Pt, Pd, Au, Ru, and Rh; The bimetallic hydrotalcite material contains two different metals selected from Co, Fe, Ni, Mg, Al, Zn, Cu and Cr; the molar ratio of the two metals is 1:3 to 1:40; The carbon carrier is one of multi-walled carbon nanotubes, conductive carbon black XC-72, graphite, conductive carbon black BP2000, and activated carbon.

3. A method for preparing a multi-metal tandem catalyst as claimed in claim 1 or 2, characterized in that: A two-step method is used, the specific steps are: (1) dispersing the carbon material carrier in a solvent, ultrasonicating for 10-40 minutes to obtain a suspension; then adding a precursor solution of a noble metal element, and stirring for 10-20 minutes; Then, an alkaline solution with a concentration of 20-40 wt% is added dropwise to the precursor solution, and the mixture is stirred for 6-15 hours. Solid particles are collected by suction filtration and dried to obtain a noble metal precursor supported on the carbon material. (2) Weigh the above-mentioned noble metal precursor loaded on the carbon material, add it to the dispersion, and ultrasonicate for 5-20 minutes; then, add the metal salt precursor and additives, place it in a 65-90°C water bath, stir for 6-20 hours, and after the reaction is completed, filter and collect the solid material, and dry it to obtain a multi-metal tandem catalyst.

4. The preparation method according to claim 3, characterized in that: In step (1): The solvent is at least one of ethanol, ethyl acetate, isopropanol, ethylene glycol, acetone and water; The precursor solution of the noble metal element is one of the hydrochloride, nitrate, acetate or chlorate of Pt, Pd, Au, Ru or Rh; The alkaline solution is one of sodium hydroxide solution, potassium hydroxide solution, sodium sulfide solution, sodium carbonate solution, potassium carbonate solution and ammonia water.

5. The preparation method according to claim 4, characterized in that: In step (2): The dispersion liquid is at least one of ethanol, ethyl acetate, isopropanol, ethylene glycol, acetone, and water; The metal salt precursor is at least two of the hydrochlorides, nitrates, acetates or chlorates of Co, Fe, Ni, Mg, Al, Zn, Cu and Cr; The additive is one of polypyrrolidone, urea, hexamethylenetetramine, sodium dodecylsulfonate and hexadecyltrimethylammonium bromide.

6. Use of the multi-metal tandem catalyst as claimed in claim 1 in preparing an electrode material for catalyzing electro-oxidation of boron hydride fuel; the electrode material comprises an electrode substrate and the multi-metal tandem catalyst layer coated on the electrode substrate; the electrode substrate is one of transparent conductive glass, glassy carbon electrode and conductive metal sheet; the effective area of ​​the conductive substrate is 0.02-0.2 cm 2 The loading amount of the catalyst layer in the electrode is 0.05-1 mg / cm 2 .

7. The use according to claim 6, wherein the preparation steps of the electrode material are: First, a multi-metal tandem catalyst is added to a mixed solution of a binder and an organic solvent, and ultrasonicated for 10-50 minutes to obtain a uniformly dispersed catalyst slurry. A certain amount of the multi-metal tandem catalyst slurry is dripped onto an electrode substrate and dried at room temperature for 2-10 hours to serve as a working electrode material for a catalyst boron hydrogen fuel electro-oxidation three-electrode system. The binder is one of a perfluorosulfonic acid resin solution, a polyvinylidene fluoride solution, a polytetrafluoroethylene solution, and a polyacrylic acid solution; The organic solvent is one of methanol, ethanol, ethyl acetate, isopropanol and dimethyl sulfoxide.

8. Use of the multi-metal tandem catalyst as claimed in claim 1 in preparing an anode electrode material for a boron hydrogen fuel cell, wherein the anode electrode material comprises a conductive substrate and the multi-metal tandem catalyst layer coated on the conductive substrate; the conductive substrate is one of carbon cloth, carbon paper, metal felt and metal foam; the thickness of the conductive substrate is 1-2 mm, and the area of ​​the conductive substrate is 2-5 cm 2 The loading amount of the catalyst layer in the electrode is 0.5-6 mg / cm 2 .

9. The use according to claim 8, wherein the anode electrode material is prepared by: First, a multi-metal tandem catalyst and a binder are added to an organic solvent, and after ultrasonication for 30-60 minutes, the catalyst is loaded onto an electrode substrate; after drying at 50-70°C, the substrate is used as an anode electrode of a single cell of direct sodium borohydride fuel at room temperature; The binder is one of a perfluorosulfonic acid resin solution, a polytetrafluoroethylene solution, and a polyimide solution; The organic solvent is one of methanol, ethanol, acetonitrile, acetone and isopropanol.

10. Use of the multi-metal tandem catalyst as claimed in claim 1 in preparing a membrane electrode material for a boron hydrogen fuel cell, wherein the membrane electrode material comprises a proton exchange membrane, the multi-metal tandem catalyst layer coated on the proton exchange membrane, and a cathode catalyst layer; the thickness of the proton exchange membrane is 10-80 μm; the cathode catalyst is a platinum carbon catalyst with a mass fraction of 20-70%, and the loading amount of the catalyst layer in the membrane electrode is 0.2-3 mg / cm 2 ; The steps of preparing the membrane electrode are: First, the multi-metal tandem catalyst and the cathode catalyst are added to the mixed solution of the binder solution and the organic solvent respectively, and after ultrasonic treatment for 10-50 minutes, a uniformly dispersed multi-metal tandem catalyst slurry and a cathode catalyst slurry are obtained. The above catalyst slurries are sprayed on both sides of the proton exchange membrane respectively, and the spraying effective area is 0.5-2cm 2 ; After being fully dried at 50-70℃ in air, it can be used as membrane electrode material for boron hydrogen fuel cells; The binder is one of a perfluorosulfonic acid resin solution, a polyvinylidene fluoride solution, a polytetrafluoroethylene solution, and a polyacrylic acid solution; The organic solvent is one of methanol, ethanol, ethyl acetate, isopropanol and dimethyl sulfoxide.